Oscillatory Dynamics in National Supply Chain Strategy: Pendulum Alignment Theory as A Framework for Resilience - R. Beniadi Setiawan (Jurnal sosial dan sains, 2026)
This article introduces Pendulum Alignment Theory (PAT) as a systems-based dynamic framework for enhancing national supply chain resilience. PAT conceptualizes strategic orientation in supply chains as an oscillatory process that fluctuates between cost efficiency, quality assurance, and responsiveness in response to external shocks and endogenous stakeholder signals. By integrating PESTEL analysis, this study operationalizes external drivers into measurable indices, thereby guiding adaptive decision-making in national logistics. The study employs a mixed-methods approach encompassing conceptual modeling, empirical indicator analysis, and scenario-based simulations. Findings indicate that political, economic, and legal shocks often trigger abrupt strategic shifts, while technological and social vectors accelerate adaptive readjustments. The results underscore the importance of capability fungibility, effective damping management, and the implementation of trigger-responsive playbooks as fundamental mechanisms of supply chain resilience. This study contributes theoretically by formalizing the dynamics of oscillation in supply chain strategy, which has been neglected in the literature. Practically, it proposes a robust governance framework for national logistics resilience, including the recommendation of establishing a national supply chain coordination institution. PAT provides a mathematical and managerial language for articulating trade-offs between cost, quality, and responsiveness, and for designing anticipatory mechanisms based on PESTEL indicator thresholds. Ultimately, this research reconceptualizes national resilience not as a static state to be achieved, but as a controlled oscillation that must be actively managed.